Kritik Metode Hermeneutika pada Al-Qur’an: Sebuah Refleksi - Bahrul Ulum (EL-BANAT: Jurnal Pemikiran dan Pendidikan Islam, 2022)
The hermeneutic approach to comprehending the Qur'an is now being debated. Some believe that because it sprang historically from Christian worries about the authenticity of their sacred text, this method is unsuited for studying the Qur’an. The goal of this study is to present a historical overview of the hermeneutical approach as a technique with methodological problems, obstacles, and potential solutions when applied to interpret the Qur’an. This research is divided into three stages: data collection, data display, and conclusion. According to the study's findings, the hermeneutic approach fosters rational supremacy and treats all texts, including human works, in the same manner. Because all books are "products of history," they can both be right and erroneous. The consequences of applying hermeneutics to the Qur’an will result in changes to existing legislation.